Moon On The Tides. (Oxford : Oxford University Press, 2010)
This anthology contains poems for GCSE English Literature Unit 2 - Poetry across time. There are four clusters of poems which are grouped by theme. Each cluster contains poems from the English, Welsh or Irish literary heritage and contemporary poems, including some poems from different cultures and traditions.
Keywords: English poetry; Literature